Peran Artificial Intelligence dalam Perpajakan terhadap Kepatuhan Wajib Pajak E-Commerce: Literasi Digital sebagai mediator - Puji Rahayu; Imarotus Suaidah (Politeknik Ganesha Medan, 2025)
In Indonesia, the development of AI technology is very rapid. This technology has been used by various sectors, one of which is the taxation sector. Even though AI has been implemented in the tax system, the use of this technology has not been maximized due to limited digital literacy among MSMEs, especially e-commerce taxpayers. The purpose of this study is to determine the effect of artificial intelligence in the taxation aspect on tax compliance with digital literacy as a mediator. The population of this study was all MSME actors who make sales through e-commerce in Kediri. The sampling technique used non-probability using the voluntary sampling method, the number of samples used was 64 respondents. The data obtained was then processed using SmartPLS software. The results of this study indicate that AI-based tax services and E-commerce Tax have an influence on digital literacy. While literasi digital also has a relationship with compliance, AI-based tax services and E-commerce Tax have no relationship with compliance. Based on the results of the path coefficient analysis, it is known that there is an indirect influence of AI-based tax services and E-commerce Tax on taxpayer compliance through literasi digital. This study concludes that while AI-based tax services and E-commerce Tax do not directly influence taxpayer compliance, they play a crucial role in enhancing digital literacy, which in turn positively impacts compliance. Therefore, improving taxpayer digital literacy through AI-driven tax education could be a key strategy to foster greater compliance among MSME actors.